The Role and Obstacles of the Indonesian Child Protection Commission in Handling Bullying - Andryawan, Andryawan; Catharina Dewi Wulansari (Journal of Law, Politic and Humanities, 2024)
The role of children is significant in bringing about changes in the nation's future. Children are expected to become individuals with noble character, and intelligence, and have a positive contribution to social life. However, children often carry out negative actions that deviate from the values and norms of society, one of which is bullying. In Indonesia, there is an institution to deal with bullying through supervision, namely the independent supervisory institution, the Indonesian Child Protection Commission (KPAI). KPAI is the government's answer to dealing with the high increase in cases of criminal acts of bullying, especially against children. This research uses a descriptive normative juridical research method with a statutory approach. Laws and problems are studied thoroughly through literature research, including legal regulations that apply in Indonesia, books, journals, expert perspectives, articles, and related issues in society. The results of this research show that KPAI has an important role as an independent institution in supervising the implementation of child protection. However, there are still many factors that hinder KPAI's movement, such as internal factors from the KPAI institutional arrangements, or external factors, namely the persistence of stigma and fear in reporting cases of violence, or the lack of legal awareness in society regarding the protection of children's rights.